Technology ethics in qualitative research: how to be - Costa, António Pedro (2021)
This introductory note stems from the organization of a special edition of articles from the World Conference on Qualitative Research. Some researchers put forth criticisms about using software in qualitative data analysis, such as losing control in the coding process and leading researchers to use a particular method of analysis according to tool characteristics. Moreover, a number of the scientists believe that the advantages of using specific tools in data analysis are numerous, such as the analysis of an enormous amounts of data, but doing research involves personal or institutional aspects that enter the field of ethics. In the case of specific qualitative data analysis software, it would be possible to list a set of principles that would begin with the organization and importing of data, proceed with their interpretative and descriptive codification followed by questioning the data, up to exporting results to their written dissemination. Such principles could set the boundaries or define ethics in the use of software, referring to any research activity that touches what is right or wrong, good or bad, moral or immoral. This text is in line with the belief shared by others that work studies that can be performed on computational ethics will influence not only the use of Qualitative Data Analysis software but also their development.